2022
DOI: 10.1007/s10900-022-01182-5
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers as Puentes/Bridges to Increase COVID-19 Health Equity in Latinx Communities of the Southwest U.S.

Abstract: This study documents the pivotal role that Community Health Workers (CHW) played while supporting underserved Latinx communities affected by COVID-19-related health inequities. With the support of CHWs’ agencies historically serving three Latinx-dense counties in Arizona, we recruited CHWs who participated in a state-wide COVID-19 testing project. Using phenomenology and narrative qualitative research methods, five focus groups were facilitated in Spanish between August and November 2021. Bilingual research te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 47 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Research on advocacy has indicated that one of the primary pre-conditions for advocacy or movement development is that certain members of society identify as a collective group that feels they have been deprived, mistreated, and have grievances directed at a system that they perceive as unjust ( 33–35 ). While CHWs in multiple countries express individual grievances with their working conditions and the public health conditions of their communities ( 1 , 11–13 , 18 , 36 ), there is less research on how CHWs identify that they share common grievances or experiences with other CHWs based on their collective role as CHWs ( 37 , 38 ). Thus, the module aims to expose CHWs to the history and background of CHW programs worldwide, explain the unique role that CHWs play in achieving universal health care globally, and share ideas for making professional CHWs a norm worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Research on advocacy has indicated that one of the primary pre-conditions for advocacy or movement development is that certain members of society identify as a collective group that feels they have been deprived, mistreated, and have grievances directed at a system that they perceive as unjust ( 33–35 ). While CHWs in multiple countries express individual grievances with their working conditions and the public health conditions of their communities ( 1 , 11–13 , 18 , 36 ), there is less research on how CHWs identify that they share common grievances or experiences with other CHWs based on their collective role as CHWs ( 37 , 38 ). Thus, the module aims to expose CHWs to the history and background of CHW programs worldwide, explain the unique role that CHWs play in achieving universal health care globally, and share ideas for making professional CHWs a norm worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also cautioned about the misuse of social media such as the spread of misinformation, bias and fear [8][9][10]. Other studies have highlighted the importance of inter-personal communication (IPC) through trusted sources such as doctors [11], and through community-based support systems [12,13] such as non-governmental organizations and health workers [14,15]. Due to multiple communication sources and a diverse media environment [16], health communication strategies were faced with the challenge of managing both the pandemic as well as an 'infodemic' [17,18] characterised by overload of information from various sources often contradictory and incorrect [19].…”
Section: Introductionmentioning
confidence: 99%